Phase-Dependent Shifting of the Adrenal Clock by Acute Stress-Induced ACTH - Engeland, William C.; Yoder, J. Marina; Karsten, Carley A.; Kofuji, Paulo (Frontiers in Endocrinology, 2016)
The adrenal cortex has a molecular clock that generates circadian rhythms in glucocorticoid production, yet it is unclear how the clock responds to acute stress. We hypothesized that stress-induced ACTH provides a signal that phase shifts the adrenal clock. To assess whether acute stress phase shifts the adrenal clock in vivo in a phase-dependent manner, mPER2::LUC mice on a 12:12h light:dark cycle underwent restraint stress for 15 min or no stress at zeitgeber time (ZT) 2 (early subjective day) or at ZT16 (early subjective night). Adrenal explants from mice stressed at ZT2 showed mPER2::LUC rhythms that were phase-advanced by ~2h, whereas adrenals from mice stressed at ZT16 showed rhythms that were phase-delayed by ~2h. The biphasic response also was observed in mice injected subcutaneously either with saline or with ACTH at ZT2 or ZT16. Blockade of the ACTH response with the glucocorticoid, dexamethasone, prevented restraint stress-induced phase shifts in the mPER2::LUC rhythm both at ZT2 and at ZT16. The finding that acute stress results in a phase-dependent shift in the adrenal mPER2::LUC rhythm that can be blocked by dexamethasone indicates that stress-induced effectors including ACTH act to phase shift the adrenal clock rhythm.